PLA-Based 3D Porous Scaffolds with Bioceramics for Load-Bearing Bone Substitutes - Ozer, Hayrunnisa; Mutlu, Büşra; Demirci, Fatma; Duman, Seyma (Springer Nature, 2025)
Three-dimensional (3D) printing technology, which has been widely adopted in the field of regenerative medicine, represents a high-speed manufacturing process for biomaterials. Three-dimensional printing technology enables the precise fabrication of biomaterial scaffolds, thereby facilitating the creation of intricate structures that are tailored to the specific characteristics of the defect site. In this study, three-dimensional printing was employed to prepare composite scaffolds comprising poly (lactic acid) and monticellite. The composite scaffolds were optimized through material characterization, mechanical testing, density measurements, and in vitro swelling assessments. The results demonstrated that the Poly (lactic acid)/monticellite composites proposed in this study were highly printable, exhibiting tunable mechanical strength and density in conjunction with the monticellite component. Additionally, the in vitro swelling properties were demonstrated to be superior to those of the neat poly (lactic acid) scaffold. This composite scaffolding of poly (lactic acid) and monticellite represents a promising strategy for load-bearing bone substitutes. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: Bioceramics; Bone tissue engineering; PLA; Scaffold